2020
DOI: 10.1186/s40645-020-00332-4
|View full text |Cite
|
Sign up to set email alerts
|

Automated collection of single species of microfossils using a deep learning–micromanipulator system

Abstract: For geochemical analysis such as stable isotope ratio, radiocarbon dating and minor element analysis for a single species of microfossils, a large number of specimens, is required. Collecting specimens one by one under a microscope requires enormous time and effort. In this study, we developed a device that automates these efforts and can be used without expert knowledge. Microfossils can be accurately classified and identified to taxonomic species level using deep learning, which is one of the learning method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…Automated picking systems that take sieved size fractions, separate them into individual particles, and image each particle may greatly reduce picking times (de Garidel-Thoron et al, 2017;Itaki et al, 2020). With samples that have already been picked and mounted, hundreds or thousands of individual microfossils can be imaged simultaneously in three dimensions and algorithmically parsed into individual images from which basic morphometric traits and features can be automatically extracted and ana-lyzed at the assemblage scale (Beaufort et al, 2014;Elder et al, 2018;Hsiang et al, 2018Hsiang et al, , 2019Kahanamoku et al, 2018).…”
Section: Microfossils and The Brave New Anthropocenementioning
confidence: 99%
“…Automated picking systems that take sieved size fractions, separate them into individual particles, and image each particle may greatly reduce picking times (de Garidel-Thoron et al, 2017;Itaki et al, 2020). With samples that have already been picked and mounted, hundreds or thousands of individual microfossils can be imaged simultaneously in three dimensions and algorithmically parsed into individual images from which basic morphometric traits and features can be automatically extracted and ana-lyzed at the assemblage scale (Beaufort et al, 2014;Elder et al, 2018;Hsiang et al, 2018Hsiang et al, , 2019Kahanamoku et al, 2018).…”
Section: Microfossils and The Brave New Anthropocenementioning
confidence: 99%
“…Images of all particles including E. antarctica valves in the prepared slides were captured using the Image Collection Unit of the miCRAD system described in Itaki et al (2020). The Image Collection Unit, which is based on "Collection Pro" from Micro Support Co., Ltd., automatically acquires digital microscopic images of particles scattered in the observation eld using an electric X-Y stage microscope controlled by a computer.…”
Section: Image Acquisition Of E Antarctica Varieties and Constructiomentioning
confidence: 99%
“…This study revealed that a model capable of detecting the ratio of two diatom species can be constructed using the miCRAD system for the rst time. The Image Collection Unit in the miCRAD system enables researches not only to obtain cropped object images for training datasets to construct CNN models, but also to conduct automated classi cation of particle images at the same time of capturing after constructing CNN models (Itaki et al, 2020). Using the model constructed in this study, automatic detection of Eucampia Index from a diatom slide can be applied to a large-scale investigation of the index variation and geographical distribution in the Southern Ocean.…”
Section: Future Perspectives For Automatic Diatom Detection Using Thementioning
confidence: 99%
See 2 more Smart Citations